Search
Ask a question
0

simplyfying algebraic expressions 9y-5y=8

9y-5y=8

 

or nine y minus 5 y equals 8

solve!

2 Answers by Expert Tutors

Tutors, sign in to answer this question.
Ksenia N. | Math Tutor - Certified Teacher will make learning funMath Tutor - Certified Teacher will make...
0

This is combing like terms before solving an equation. As you see both of these terms have the same variable "y". This means we are talking about the same thing. So:

9y-5y=8

First combine like terms: 9y-5y and you get 4y

4y=8  (because y is multiplied to get it back we have to divide- divide by 4 on both sides)

and we get: y=2

you can check your answer by "plugging" your answer for "y" and see if you get "8" :

9(2)-5(2)=8

18-10=8

8=8 means your answer is right:)

Asok B. | Ph. D in Biochemistry, willing to teach Chemistry, Biochemistry, MathPh. D in Biochemistry, willing to teach ...
4.7 4.7 (18 lesson ratings) (18)
0

9y-5y=8

hence 4y=8

y=2